Performance modeling and evaluation of transportation systems using analytical recursive decomposition algorithm for cyclone mitigation. Issue 5 (4th July 2019) - Gupta, Sachin; Gupta, Bhoomi
Abstract: Emergencies place demands on communication techniques that are frequently different from the demands of non-emergency circumstances. Message prioritization, computerization of correspondence, quick message conveyance and different facilities are regularly needed by every emergency circumstance. Lacking crisis correspondence capabilities can have results that are inconvenient and devastating at worst. Ensuring that such systems have inherent redundancies for geo-location message focusing on using multiple map providers like Google, OpenStreetMap, etc. will need to turn into the standard. Furthermore, utilizing standard push notification gateways, and taking into consideration different operating modes for the emergency alert system, contingent on information system accessibility, will help to guarantee the framework's utility and effectiveness. The objective of this paper is to develop a risk assessment model in the case of natural calamities such as a cyclone and create an effective evacuation model for residents of the area by calculating the effective performance of the usual means of transportation using suitable performance metrics.